PEMANFAATAN TEKNOLOGI DIGITAL DALAM MENDUKUNG PEMBELAJARAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Mustika Indah, Pratiwi; Wilujeng, Rena; Sekarningrum, Nisrina; Rahmadhani, Mutiara; Aini, Dewi Nur; Indrawati, Delia; Imaduddin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research seeks to explore the application of digital technology in enhancing inclusive learning for students with special needs at the elementary school level. A qualitative research method is used through a review of literature by examining pertinent scientific studies published in the past decade. Results reveal that digital tools like interactive educational apps, audio-visual resources, and assistive technologies (including text-to-speech, speech-to-text, and screen reading software) significantly contribute to better accessibility, comprehension, and motivation for learning among students with special needs. Additionally, employing the Universal Design for Learning (UDL) and Technological Pedagogical Content Knowledge (TPACK) frameworks allows educators to create flexible and student- focused learning environments. Nevertheless, real-world application encounters obstacles such as inadequate infrastructure, unequal access to technological resources, and low digital proficiency among teachers. As a result, coordinated initiatives, including thorough training for educators, creation of inclusive digital educational tools, and robust policy endorsement, are essential. Effective incorporation of digital technology has the potential to promote more efficient, fair, and adaptive inclusive education for a variety of learners